SOLAR POWER AND ECO-FRIENDLY CONFERENCES AS CORRELATES OF AIR AND LAND POLLUTION IN LISTED BEVERAGE FIRMS IN IMO AND ABIA STATES - Njoku, Kenneth Chukwudi; Onuegbu, Remigius Chinedu; Ugo, Chukwunenye Jude (African Journal of Social and Behavioural Sciences, 2024)
Huge research gaps exist as it relates to the use of solar power and eco-friendly business conferences in businesses in Imo and Abia States. This research problem necessitated this present study. The objectives of the study were to examine the relationship between use of solar panels and reduced air pollution as well as assess the extent to which eco-friendly business conferences influence the reduction of air pollution and land pollution in the listed beverage firms. The researchers employed the survey research design in the research. A structured questionnaire was the major instrument for data collection. Cronbach Alpha statistic was used to obtain a reliability ratio of 0.85. Data analysis was committed to descriptive statistics. Correlation analysis was used to test hypotheses. The study found positive and significant relationships between the use of solar panels and reduced air pollution; the use of eco-friendly business conferences and reduction of air pollution; and the use of eco-friendly business conferences and reduced land pollution in the listed firms. These findings constitute a major contribution to empirical literature on the use of solar power and eco-friendly conferences in listed beverage firms. It was concluded that solar power and eco-friendly business conferences are correlates of air and land pollution in listed beverage firms in Imo and Abia States. The study recommends, among others, that management should make more efforts to expand the use of solar energy so as to reduce air pollution for business premises preservation.